ANCIENT SARYNS OF THE GREAT STEPPE - T. B. Gafurbekov; A. K. Omarova; A. Zh. Kaztuganova (Scientific Journal of Pedagogy and Economics, 2019)
In the program article “Seven Facets of the Great Steppe”by N.A.Nazarbayev the assignments are designated, which assume the implementation of a set of measures aimed at their informational support and phased implementation. It emphasizes that “... weneed to publish a collection “Ancient motifs of the Great Steppe”- a collection of significant works created for traditional Kazakh musical instruments: kobyz, dombyra, sybyzgy, sazsyrnay etc. The folklore and melodies of the Great Steppe should acquire “a new breath” in a modern digital format” [1, 4 p.]. Currently the main goal of the joint efforts of scholars in folklore studies (philology and art history) is to collect the ancient motifs of the Kazakh people, determine their best variants in rites and customs, kuy for kobyz, dombyra, sybyzgy and sazsyrnay, epic and song poetry, present selected patterns in musical notation, audio, video materials and scientific comments in three languages (Kazakh, Russian and English) in digital format as relevant intellectual products. The proposed “steps”, which have a humanitarian focus, are significant at national and international scale. The best patterns of musical heritage of the Kazakh people, first presented in digital format in the Anthology “Uly dalanyk kone saryndary” (“Ancient Saryns of the Great Steppe”) with notation texts, adapted scientific comments in three (Kazakh, Russian and English) languages (with online application), are in demand not only in educational and pedagogical activities of the academic and teaching staff of various universities, in general publicity, but also in the process of their popularization in the global space.